A novel MC1R allele for black coat colour reveals the Polynesian ancestry and hybridization patterns of Hawaiian feral pigs. Issue 9 (September 2016) - Linderholm, Anna; Spencer, Daisy; Battista, Vincent; Frantz, Laurent; Barnett, Ross; Fleischer, Robert C.; James, Helen F.; Duffy, Dave; Sparks, Jed P.; Clements, David R.; Andersson, Leif; Dobney, Keith; et al.
Abstract : Pigs ( Sus scrofa ) have played an important cultural role in Hawaii since Polynesians first introduced them in approximately AD 1200. Additional varieties of pigs were introduced following Captain Cook's arrival in Hawaii in 1778 and it has been suggested that the current pig population may descend primarily, or even exclusively, from European pigs. Although populations of feral pigs today are an important source of recreational hunting on all of the major islands, they also negatively impact native plants and animals. As a result, understanding the origins of these feral pig populations has significant ramifications for discussions concerning conservation management, identity and cultural continuity on the islands. Here, we analysed a neutral mitochondrial marker and a functional nuclear coat colour marker in 57 feral Hawaiian pigs. Through the identification of a new mutation in the MC1R gene that results in black coloration, we demonstrate that Hawaiian feral pigs are mostly the descendants of those originally introduced during Polynesian settlement, though there is evidence for some admixture. As such, extant Hawaiian pigs represent a unique historical lineage that is not exclusively descended from feral pigs of European origin.